Prevalencia de Nematodos Gastrointestinales en Sistemas de Producción Ovina y Caprina bajo Confinamiento, Semiconfinamiento y Pastoreo en Municipios de Antioquia, Colombia - Zapata Salas, Richard (2016)
The aim of this study was to determine the prevalence of gastrointestinal nematodes in sheep and goat production systems in the tropics of Antioquia, Colombia through a cross-sectional study. Faecal samples were collected from 302 sheep and goats from 17 farms in 9 municipalities. The prevalence of nematode infection and the parasite burden based on species and genus identified through taxonomic characterization of infective third-stage larvae (L3) and considering clinical and epidemiological variables were evaluated. The prevalence of infected ruminants was 76%, where 69.5% showed low parasite burden (less than 200 epg of faeces). It is concluded that ovine and caprine farms in Antioquia had high prevalence of Trichostrongylids infection, where Haemonchus contortus (61.3%), Teladorsagia (Ostertagia) circumcincta (25.5%) and Trichostrongylus sp (21.5%) were the most common parasites.